RESPON PEMBERIAN MACAM PUPUK KANDANG DAN PESTISIDA NABATI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG HIJAU (Vigna radiata L.) - Emmy Hamidah; Khoirul Anwar; Dian Eka Kusumawati (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2024)
Green bean plants (Vigna radiata L.) are one of the very good food crops to be cultivated in tropical areas such as Indonesia, however the need for green beans in Indonesia is still imported. One of the causes of low production of green beans (Vigna radiata L.) is low soil fertility. Efforts to increase soil fertility include providing nutrients through organic fertilization and vegetable pesticides. This research used a factorial randomized block design (RAKF) with 2 factors, each factor consisting of 3 levels with 3 replications. The first factor is the type of organic fertilizer: without manure, goat manure and cow manure. The second factor is types of vegetable pesticides: without vegetable pesticides, garlic pesticides and papaya leaf pesticides. Data from observations for each parameter were analyzed using Fisher's test (F test) at the 5% level, and if significant differences were found, it was continued with the most significant difference test (BNT). The research results showed that the use of goat manure and vegetable pesticides made from garlic gave the best results compared to other treatments.